A case of multiple glucagonomas with no clinical manifestations of excess glucagon despite hyperglucagonemia. Issue 1 (27th March 2023) - Amano, Shogo; Suenaga, Shigeyuki; Hamamoto, Kaori; Yada, Shoko; Tsuyama, Takanori; Shinoda, Shuhei; Tanaka, Yuya; Takemoto, Yoshihiro; Harada, Eijiro; Tanabe, Katsuya; Asahara, Shunichiro; Hoshii, Kazunobu; et al.
Abstract: Herein we report the case of a patient with multiple glucagonomas that have been precisely described with endoscopic ultrasound. A 36‐year‐old woman was referred to our hospital for computed tomography investigation of multiple pancreatic masses. Physical examination was unremarkable; on contrast‐enhanced computed tomography, mass lesions were evident in the head, body, and tail of the pancreas. The mass in the pancreatic head was poorly demarcated and exhibited a faint contrast effect, the one in the pancreatic body was a cystic lesion, and the one in the pancreatic tail was hypervascular. Blood investigations showed that serum glucagon was abnormally high at 7670 pg/ml; glucose tolerance was not impaired. There was no family history that suggested multiple endocrine neoplasia type 1 or von Hippel‐Lindau disease. Endoscopic ultrasound revealed that there were additional masses, which were scattered isoechoic to hyperechoic lesions a few millimeters in size. Ultrasound‐guided fine needle biopsy of the lesion in the pancreatic tail resulted in a diagnosis of a neuroendocrine tumor. Based on these pathologic findings, we performed a total pancreatectomy. A large number of nodules with tumor cells were evident in all cut surfaces of the surgical specimen. Immunostaining was positive for chromogranin A and glucagon, and glucagonoma was therefore diagnosed. It is conceivable that attenuated glucagon action could have contributed to the development of the multiple glucagonomas.